Atraumatic Limping Child, a Challenge for Pediatricians: An Observational Age-Related Study in a Pediatric Emergency Department - Sebastian Cristaldi; Alessandra Boni; Valentina Ferro; Antonio Musolino; Nicoletta Della Vecchia; Elena Boccuzzi; Elena Bellelli; Francesco Saverio Biagiarelli; Angelo Gabriele Aulisa; Marco Cirillo; Umberto Raucci; Alberto Villani (MDPI AG, 2024)
Background: Atraumatic limping is a frequent cause of consultation in Pediatric Emergency Departments (PED) and often represents a challenge for pediatricians for its variability in etiology ranging from benign causes to potential crippling conditions. The aims of this research are to illustrate the clinical features of acute limping children (LC) and to identify the possible red flags that could help to make a diagnosis of severe pathologies. Methods: We carried out a retrospective study about non-traumatic limping children referred to the PED of Bambino Gesù Children's Hospital over a 2-year period. We divided the cohort into three groups based on the patient's age: toddlers, children and adolescents. We considered crippling conditions: oncologic etiologies, bone or neurological infections, epiphysiolysis, Perthes disease, Guillain Barrè syndrome and non-accidental injuries. Results: We analyzed 485 patients. At clinical evaluation, 19.5% of the patients presented at least one sign and/or symptom of red flags. Crippling conditions (6.2% of the total population) showed red flags in 36.7%. Transient synovitis of the hip was the most frequent diagnosis. We found crippling conditions in 30 patients, mostly represented by toddlers. Conclusions: Our data suggest that toddlers and patients presenting red flags should be evaluated with particular suspicion because they have an increased risk of underlying severe conditions.